EXPLORING THE CONVERGENCE OF IOT AND SMART HOME TECHNOLOGIES: A LITERATURE REVIEW OF INTEGRATION AND INNOVATION PATHWAYS - Mira Wellya Fatma; Maresa Prasafitri; Al Amin (Adisam Publisher, 2025)
This study aims to explore the convergence of Internet of Things (IoT) and smart home technologies through a systematic literature review. The main objective is to identify key integration frameworks, interoperability challenges, security and privacy issues, and emerging innovation pathways that shape the evolution of IoT-based smart home ecosystems. Design/Methodology/Approach – A Systematic Literature Review (SLR) approach was employed following the PRISMA protocol. Academic publications indexed in Scopus, IEEE Xplore, and ScienceDirect from 2013 to 2024 were systematically screened. Inclusion criteria focused on studies addressing IoT-smart home integration, interoperability, efficiency, security, and innovation. Data were analyzed qualitatively using thematic content analysis to extract major research themes and identify research gaps. Findings –The review identifies four dominant research themes: (1) Architectural integration leveraging sensing, networking, and application layers with cloud and edge computing; (2) Interoperability challenges due to fragmented platforms and lack of global standards; (3) Security and privacy concerns involving data breaches, unauthorized access, and system vulnerabilities; and (4) Technological innovation driven by Artificial Intelligence (AI), Machine Learning (ML), blockchain, and 5G technologies. Despite significant progress, the literature highlights the need for adaptive integration frameworks, AI-based security mechanisms, and empirical evaluation of hybrid IoT–AI–Blockchain systems. Originality/Value – This study provides a comprehensive synthesis of recent advances in IoT-smart home research, mapping existing frameworks and identifying unresolved issues. It contributes to the body of knowledge by offering a conceptual foundation for future interdisciplinary research, practical implementation strategies, and policy development for secure, efficient, and user-centric smart home ecosystems.